Economic Learning: Implementation of Tourism Strategy in Driving Local Economy - Putri, Chamelia; Wulandari, Putri; Hartanto, Wiwin (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2025)
This study aims to find the best way to teach the concept of economic growth to students. The research method uses mixed methods, namely qualitative methods with interpretative phenomenological analysis techniques that aim to find out the best way to teach economic material the concept of economic growth and quantitative methods with descriptive analysis techniques to prove the occurrence of economic growth in Banyuwangi Regency and the strategies carried out by the tourism sector to encourage growth that occurs. Banyuwangi Regency was chosen because it is an area that has experienced accelerated economic growth in Indonesia. The results showed that the best way to teach the concept of economic growth is with the tourism economy, which is the direct involvement of students in experiential education activities to provide contextual understanding that encourages the development of soft skills, critical thinking, and cross-sectoral understanding that is needed in real life. Keywords: economic learning, local economic growth, tourism economy